Augmenter of liver regeneration ameliorates renal fibrosis in rats with obstructive nephropathy. Issue 5 (5th September 2014) - Chen, Guo-tao; Zhang, Ling; Liao, Xiao-hui; Yan, Ru-yu; Li, Ying; Sun, Hang; Guo, Hui; Liu, Qi
Abstract : Renal fibrosis is a hallmark in CKD (chronic kidney disease) and is strongly correlated to the deterioration of renal function that is characterized by tubulointerstitial fibrosis, tubular atrophy, glomerulosclerosis and disruption of the normal architecture of the kidney. ALR (augmenter of liver regeneration) is a growth factor with biological functions similar to those of HGF (hepatocyte growth factor). In this study, our results indicate that endogenous ALR is involved in the pathological progression of renal fibrosis in UUO (unilateral ureteral obstruction) rat model. Moreover, we find that administration of rhALR (recombinant human ALR) significantly alleviates renal interstitial fibrosis and reduces renal-fibrosis-related proteins in UUO rats. Further investigation reveals that rhALR suppresses the up-regulated expression of TGF-β1 (transforming growth factor β1) induced by UUO operation in the obstructed kidney, and inhibits Smad2 and Smad3 phosphorylation activated by the UUO-induced injury in the animal model. Therefore we suggest that ALR is involved in the progression of renal fibrosis and administration of rhALR protects the kidney against renal fibrosis by inhibition of TGF-β/Smad activity.